Characterization of bla-tem and bla-shv genes from bacterial isolates of various environmental soil samples in Kampar - Bu, Kah Yee (2023)
The illegal disposal of municipal wastes that contain antibiotics or antimicrobial drugs can cause selection pressure to act on the soil microbial community, leading to the emergence of resistance toward currently available antibiotics. Beta lactamases are a group of enzymes that are capable of hydrolyzing the beta-lactam antibiotics which could potentially evolve and lead to the formation of extended spectrum beta-lactamases. Beta-lactamases are capable of hydrolyzing broad spectrum antibiotics has posed challenges in disease control. The purpose of this study was to characterize and amplify the bla-TEM and bla-SHV homologous genes. Fourteen bacterial isolates were successfully isolated from various soil samples in Kampar by isolation carried out on LB media that was supplemented with ampicillin. Further, characterization of the bacterial isolates were performed using selected biochemical tests. PCR amplifications were performed using corresponding bla-TEM primers and bla-SHV primers on bacterial isolates designated as 3P, 7P, 3, 7 and 10 and they consist of DNA fragment corresponding to approximately 870 base pairs. BlastX alignment search was carried out. Subsequently, the nucleotide sequences were translated into protein sequences for multiple sequence alignment and phylogenetic tree analysis was done. Based on the result, 3P was identified as TEM class A beta-lactamase, while 7P and 10 were iii classified as SHV class A beta-lactamase and LEN class A beta-lactamases respectively. On the other hand, translated gene fragment of 3 and 7 corresponded to broad spectrum OKP-B beta-lactamases. Based on phylogenetic analysis, bacterial isolate 3 and 7 belong to sister group. On the other hand, 7P and 10 also identified as sister group, but 10 was outgroup